PENGENALAN DAN IMPLEMENTASI TONG SAMPAH PINTAR PADA WARGA RT 08 DESA CIBODAS - Zulfikar, Zulfikar; Witonohadi, Amal; Anselmo Paulus Sima, Harold; Ciputra, Kristian; Ersinalsal Ginting, Rayhan (Universitas Trisakti, 2025)
Waste management in RT 08 Cibodas Village still uses traditional methods that are less effective and risk polluting the environment. Therefore, it is necessary to hold community service activities that aim to introduce and apply smart trash bins to RT 08 Cibodas Village residents as an innovative solution in waste management. This activity also educates the community about the importance of saving energy and protecting the environment to increase awareness of environmental sustainability. The implementation of PKM activities includes observation and interviews, needs analysis, delivery of materials, and demonstrations and grants of tools to residents. The pre-test results showed that most residents were not familiar with the concept of technology-based waste sorting. In contrast, the post-test showed an increase in their understanding and interest. In addition, 91.8% of participants considered this helpful activity, and it was conducted to add new insights into technology-based waste management. Hopefully, this innovation can be implemented sustainably to create a cleaner and healthier environment.